Synthesis and Antimicrobial Activities of 1,2,4-Triazole and 1,3,4-Thiadiazole Derivatives of 5-Amino-2-Hydroxybenzoic Acid - Sabir Hussain; Jyoti Sharma; Mohd Amir (E-Journal of Chemistry, 2008)
Various 4-amino-2-[4-(4-substituted phenyl)-5-sulfanyl-4H-1,2,4-triazol-3-yl] phenol (4a-c), 4-amino-2-{4-amino-5-[(4-substituted phenyl)amino]-4H-1,2,4-triazol-3-yl} phenol (5a-c) and 4-amino-2-{5-[(4-substituted phenyl)amino]-1,3,4-thiadiazole-2-yl} phenol (6a-g) were synthesized and evaluated for their antibacterial and antifungal activity. The compounds showed significant antibacterial activity against S. aureus (gram-positive) and E.coli (gram-negative) bacteria and antifungal activity against A. niger fungi using cup plate technique